2017
DOI: 10.1016/j.brs.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Neural activity during attentional conflict predicts reduction in tinnitus perception following rTMS

Abstract: Background Subjective idiopathic tinnitus is an intrusive, distracting, and potentially disabling disorder characterized by phantom perception of sounds. Although tinnitus has no approved pharmacologic treatment, recent evidence supports the use of repetitive transcranial magnetic stimulation (rTMS) to alleviate tinnitus symptoms. Objective/Hypothesis Repetitive TMS delivered over the middle superior temporal gyrus (STG) may alter ratings of tinnitus awareness and annoyance more than loudness due to change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…sham rTMS Anders M 2010 [26] Czech Republic [27] The Netherlands [30] The USA [31] The USA James G 2018 [32] The USA [34] The USA Godbehere J 2019 [36] The…”
Section: Resultsmentioning
confidence: 99%
“…sham rTMS Anders M 2010 [26] Czech Republic [27] The Netherlands [30] The USA [31] The USA James G 2018 [32] The USA [34] The USA Godbehere J 2019 [36] The…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with recent reports of an association between tinnitus and 2 major networks: a frontoparietal network, regulating cognitive control of attention, and a cinguloinsular saliency network, mediating pain and emotion. 63 The mechanisms underlying paired-pulse suppression are attributable to both presynaptic and postsynaptic GABAergic inhibition. The adaptation in the paired-pulse response depends on the interstimulus interval (ISI) between the adapter (PP-S1 in the current study) and adapted (probe, PP-S2 in the current study).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with recent reports of an association between tinnitus and 2 major networks: a frontoparietal network, regulating cognitive control of attention, and a cingulo-insular saliency network, mediating pain and emotion. 63…”
Section: Methodsmentioning
confidence: 99%
“…Frontothalamic gating system may be formed by limbic and paralimbic structures for tinnitus [110]. James et al's study demonstrated with functional MRI that left superior dorsolateral prefrontal cortex had a greater role in predicting tinnitus awareness [111]. Combined prefrontal and temporal cortex rTMS was found to be more effective than temporal cortex rTMS alone [101,[112][113][114].…”
Section: Tms In the Treatment Of Tinnitusmentioning
confidence: 99%
“…Khedr et al suggested that 10 or 20 Hz stimulation could also be effective [123]. James et al's study demonstrated that 1 Hz rTMS seemed to significantly decrease the awareness, loudness, and annoyance of tinnitus, but 10 Hz stimulus seemed to decrease only the awareness of tinnitus [111].…”
Section: Tms In the Treatment Of Tinnitusmentioning
confidence: 99%